Verticillium dahliae Disease Resistance and the Regulatory Pathway for Maturity and Tuberization in Potato. Issue 1 (1st March 2018) - Tai, Helen H.; De Koeyer, David; Sønderkær, Mads; Hedegaard, Sanne; Lagüe, Martin; Goyer, Claudia; Nolan, Lana; Davidson, Charlotte; Gardner, Kyle; Neilson, Jonathan; Paudel, Jamuna Risal; Murphy, Agnes; et al.
Abstract : Verticillium dahliae Kleb. is a pathogenic fungus causing wilting, chlorosis, and early dying in potato ( Solanum tuberosum L.). Genetic mapping of resistance to V. dahliae was done using a diploid population of potato. The major quantitative trait locus (QTL) for Verticillium resistance was found on chromosome 5. The StCDF1 gene, controlling earliness of maturity and tuberization, was mapped within the interval. Another QTL on chromosome 9 co‐localized with the Ve2 Verticillium wilt resistance gene marker. Epistasis analysis indicated that the loci on chromosomes 5 and 9 had a highly significant interaction, and that StCDF1 functioned downstream of Ve2 . The StCDF1 alleles were sequenced and found to encode StCDF1.1 and StCDF1.3. Interaction between the Ve2 resistance allele and the StCDF1.3 was demonstrated, but not for StCDF1.1 . Genome‐wide expression QTL (eQTL) analysis was performed and genes with eQTL at the StCDF1 and Ve2 loci were both found to have similar functions involving the chloroplast, including photosynthesis, which declines in both maturity and Verticillium wilt. Among the gene ontology (GO) terms that were specific to genes with eQTL at the Ve2, but not the StCDF1 locus, were those associated with fungal defense. These results suggest that Ve2 controls fungal defense and reduces early dying in Verticillium wilt through affecting genetic pathway controlling tuberization timing.